Thin ZIF-8 nanosheets synthesized in hydrophilic TRAPs. Issue 30 (12th July 2021) - Sasaki, Koki; Okue, Tsuyoshi; Shu, Yasuhiro; Miyake, Koji; Uchida, Yoshiaki; Nishiyama, Norikazu
Abstract : Several nm thick ZIF-8 nanosheets can be synthesized from multiple hydrophilic precursors in the hydrophilic space inside bilayers in a decane solution of the amphiphile Brij L4. Abstract : The preparation method of nanosheets using hyperswollen lyotropic lamellar phases, the 'two-dimensional reactor in amphiphilic phases (TRAP) method', has successfully provided nanosheets of various non-layered materials. Previously reported examples started from a single hydrophobic or hydrophilic precursor and multiple hydrophobic precursors. Here, we propose a synthesis method of nanosheets of ZIF-8, zinc 2-methylimidazolate, with a sodalite-like framework. They grow up to a few nanometers of thickness and several hundred nanometers of width with neither aggregation nor impurities from multiple hydrophilic precursors in the stoichiometric ratio inside the hydrophilic TRAPs consisting of the amphiphile Brij L4. The thin nanosheets of ZIF-8 doped with Co 2+ (Co-ZIF-8) synthesized by the same method maintained a high specific surface area after calcination. Therefore, the oxygen reduction reaction (ORR) activity of the calcined Co-ZIF-8 NSs for fuel cells becomes higher than that of the calcined conventional Co-ZIF-8 crystals.